LYMPH NODE METASTASIS CHARACTERISTICS AND SURVIVAL OUTCOMES AFTER VIDEO ENDOSCOPIC INGUINAL LYMPHADENECTOMY FOR PENILE CANCER (Vietnam Journal of Community Medicine, 2026)
Objectives: To characterize inguinal lymph node metastasis and evaluate survival outcomes after video endoscopic inguinal lymphadenectomy (VEIL) in penile cancer patients, and to identify predictors of nodal metastasis.Methods: A prospective descriptive case series of 38 penile cancer patients who underwent bilateral VEIL at Binh Dan Hospital from May 2023 to June 2025. Analysis included lymph node metastasis characteristics (pN staging, extranodal extension), predictors of pN positivity using Fisher’s exact test, and survival outcomes (disease-free survival, overall survival).Results: The pN (+) rate was 21.1% (8/38 patients): pN1 = 13.2% (n = 5), pN2 = 7.9% (n = 3). No pN3 cases were identified. Extranodal extension was detected pN (+) in 1/8 patients (12.5%). Mean node yield was 15.9 ± 2.3 nodes (13-23 nodes)/patient. Positive fine needle aspiration had a positive predictive value of 100%; fine needle aspiration is, however, a cytological confirmation test rather than an independent predictor. Lymphovascular invasion, perineural invasion, and G2/G3 grading showed non-significant trends toward pN (+) (p > 0.05). At data cut-off 30 June 2026, median follow-up was 32.5 months (range 1.3-47.0); mean disease-free survival was 25.6 months; recurrence rate was 15.8% (6/38). A non-significant trend toward longer disease-free survival was observed in the pN0 group (27.2 months) versus the pN (+) group (19.4 months). 10.5% patients received adjuvant chemotherapy.Conclusion: VEIL provides accurate lymph node staging with a 21.1% pN (+) rate. Positive fine needle aspiration is the most predictive factor for nodal metastasis. Survival outcomes are acceptable with a mean disease-free survival of 25.6 months. Lymphovascular invasion, perineural invasion and G2/G3 grading showed non-significant trends toward pN (+).
Keywords: Penile cancer, inguinal lymph node metastasis, VEIL, pN staging, survival outcomes, predictors.